What al-Qatrab uniquely mentioned about Yunus bin Habib in the topics of "Waquf" (pause) and "Imāla" (tilting of vowel sounds) - Al-Zahrani, Saad Mohammed (Journal of Arabic Language Sciences and Literature, 2024)
The research aimed to uncover the views of Yunus bin Habib on "waquf" and "imāla" that were uniquely recorded by al-Qatrab in his book Ma'ani al-Qur'an and Tafseer Mushkil I'rab, and to clarify his position on them, whether agreeing or disagreeing.The research was divided into two sections, preceded by an introduction and followed by a conclusion, which includes a list of sources and references. The introduction discussed the research problem, its importance, its questions, and its methodology, followed by the structure of the research. The two sections addressed the following: the first discussed Yunus bin Habib's views on "waquf", and the second addressed his views on "imāla".The research adopted a descriptive methodology, which involved describing the collected material after gathering it, classifying and analyzing it, presenting scholars' views on it, and then discussing and possibly weighing them.The research concluded with several results, which were mentioned in the conclusion, the most important of which were:1.Al-Qatrab's unique mention of Yunus' views on "waquf" and "imāla", some of which were not previously recorded, especially in Sibawayh's book, while some had been mentioned but not attributed to Yunus; only al-Qatrab attributed them to him.2. Al-Qatrab's stance on Yunus' views was fair and moderate, neither biased in favor of nor against them. This is evident from his agreement with some views and disagreement with others.
Keywords: Unique; Yunus; al-Qatrab; Waquf; Imāla